THE EFFECTIVENESS OF USING LINKTREE AND WORDWALL APPLICATIONS ON IPS LEARNING OUTCOMES FOR CLASS V SDN CILANGKAP 01 - Bella Santika Retna Ningtyas; Mimin Ninawati (Faculty of Social and Political Sciences University of Bangka Belitung, 2021)
In this globalization era, information technology has rapidly grown, and it gives a huge effect on the education field. The use of application technology in the world of education is unavoidable today. Because of this covid-19 pandemic, online learning has been a new mode and the education institutions inevitably should use the application technology in their learning process. This research suggests Linktree and Wordwall as new alternatives that can be used by the student in the learning process. This research focuses on the effectiveness of using Linktree and Wordwall applications on IPS learning outcomes of the student class V. This research is quantitative research with a correlational approach. This approach is used to reveal the relationship and the level of the relationship between two or more variables. The result of the research is described based on the obtained data from the questionnaires and tests. The results of this study indicate that there is a significant relationship between the use of Linktree and Wordwall applications on Social Studies Learning Outcomes for Class V students with a correlation coefficient between X1 and Y of 0,365. The provisions of the correlation test by comparing rcount > rtable (0,365 > 0,355) and p-value of 0,022 < 0,05. Therefore, there is a significant relationship between X1 and Y. The correlation coefficient between X2 and Y of 0,477 > rtable 0,355. The provisions of the correlation test by comparing rcount > rtable = 0,477 and p-value of 0,003 < 0,05. By this result, it can be concluded that the relationship X2 and Y is significant.